Mortimer Taube and his legacy: between technical and scientific production - Keitty Vieira; Cezar Karpinski (Transinformação, 2024)
Abstract This article deals with the life and work of Mortimer Taube, an American philosopher and librarian who contributed to the organization and representation of information and knowledge, and to the retrieval of information. Even if Taube does not identify yourself as a librarian, philosopher, documentalist or information scientist, your technical and scientific production brings him closer to the notion of Information that is currently studied by Information Science, Therefore, this article aims to study his work from this perspective. This is because Taube was the creator of the Uniterm System, a pioneer in post-coordinated indexing. He was the founder of Documentation Incorporated, a company that provided information services to renowned institutions such as the National Aeronautics and Space Administration and the United States Air Force. It was a qualitative, exploratory, bibliography and documentation study, without chronological limit, and the sources used were: Association for Information Science and Technology; Columbia University; Duke University; Library of Congress; Journal Storage; NASA’s Library; University of Chicago Press Journal, and Library Quarterly. Were analyzed 52 documents, the oldest publication dates from 1936 and, the most current, from 1965. It is concluded that Taube’s legacy was the contribution in the area of indexing and information retrieval, as well as his critical position on librarianship and information science. In general, the philosophical influence of Taube’s education was reflected in his bibliographic production, spread among the formulation of concepts, theoretical foundations, and perspectives disseminated by the author.